Aspectos filosóficos e atemporais da teoria política de Maquiavel - Guerra, Avaetê de Lunetta e Rodrigues (2021)
In this work, it is an about analyzing Machiavelli’s ideas and contributions to 16th- century Italy, when the Renaissance reached its peak, witnessing political facts involving his hometown, Florence, where there was a great desire on the part of the population that aimed for changes, inspiring the sage Florentino in your writings and thoughts, thus generating a strong feeling of hope in a political unity. The present work investigates topics related to the Trecento and Quattrocento periods, fundamental in the construction of the Italian political model of the time, presenting the historical influences that led Nicolau Machiavelli to develop your theories. The research was developed based on the works The Prince and Discorsi, in addition to the contributions of important commentators. The research hypothesis of this dissertation, states that Machiavelli was responsible for the "invention" of a political theory of its own and innovative for the time, demystifying the idea that Florentino would be only a revealing agent of the facts that were happening in his time. The research method will aim to demonstrate that, although not having a moralistic character, Machiavelli was able to establish fundamental principles of human conduct in the philosophical sense, by analyzing aspects of the political reality of the time, establishing a new look, in an attempt to investigate what it is possible and efficient in the universe of alternatives to those who seek victories in their practices and actions, drawing lessons from previous events, which will make all the difference in the formulation of their political theory. It also discusses the concept of virtù, a term used by the author in this writings and frequently addresses by philosophers and researchers from different eras, making an analysis of the works Discorsi and “The prince” as a work of advice to new rules, exploring some consequences of these approaches. Finally, in the last chapter, we will make an overview of the ethical and religious issues witnessed by the author, discussing religion and politics, dialoguing with the reference biographies, aiming at a greater understanding about the philosophical contributions brought by Machiavelli to Italy at the time.